The Impact of Technology-Enhanced Instruction on Student Achievement: A Comparative Study Using MAP and CAT 4 Data - DIB, ELISE (2025)
Technology-enhanced instruction (TEI) is transforming modern educational systems, yet its impact on student academic achievement remains a critical area of investigation.This study examines TEI’s impact on student academic achievement across multiple subjects while considering the students’ cognitive profiles and grade levels. The research analyses data from 3,327 students in Grades 3 to 9 across five UAE schools adopting the American curriculum, encompassing 9,264 MAP assessments in English language, English reading, math, and science. The study uses a quantitative approach to evaluate the relationship between TEI, academic achievement, cognitive profiles, and grade levels. Findings indicate that TEI has a modest but significant impact on academic achievement with varying effects across subjects. Math shows the strongest positive relationship, while science demonstrates a complex non-linear relationship with negative results at high levels of technology integration. English language and reading show marginal positive correlations. Additionally, results reveal that students with verbal bias outperform their peers, though CAT 4 cognitive profiles do not moderate the relationship between technology integration and MAP scores. Grade level emerges as the strongest predictor of MAP scores. The findings of the study suggest that technology integration strategies should be subject-specific, with an emphasis on math. This study contributes to the growing body of literature on educational technology by offering evidence-based recommendations on technology integration in UAE schools and international schools with similar contexts.